Assessing the Sustainability of the Culinary Cafe Business Through Business Suitability Analysis - Dessy Agustina; Teguh Anshory; Andrey Andrey (TourEcon: International Journal of Tourism and Economic Studies, 2024)
This research evaluates the sustainability of the culinary cafe business through business suitability analysis. This research aims to assess whether culinary cafes have adequate business suitability to achieve long-term sustainability. The business suitability analysis method is used to identify factors that influence the success and sustainability of a culinary cafe business. Primary and secondary data were analyzed to support this evaluation. The research findings highlight the importance of factors such as location, target market, competition, and environmental policies in determining the sustainability of a culinary cafe business. The practical implications of this research can help business owners and entrepreneurs to make better decisions in managing and developing a culinary cafe business in a sustainable manner.